Long-lasting actions of somatostatin on pyramidal cell excitability in the mouse cingulate cortex. (17th April 2019) - Riedemann, Therese; Sutor, Bernd
Highlights: Somatostatin induces long-lasting and reproducible reductions in cell excitability in pyramidal neurons of the cingulate cortex. Desensitization of the somatostatin receptor became evident only during repetitive applications of high concentrations of the neuropeptide. The observed decrease in efficacy is not mediated via the G-protein-coupled receptor kinase 2. Abstract: Many neurological diseases are related to disturbances of somatostatin- (SOM-) expressing interneurons in the cingulate cortex. Therefore, their role within the circuitry of the cingulate cortex needs to be investigated. We describe here the physiological time course of SOM effects onto pyramidal cell excitability and action potential discharge pattern. Furthermore, we show that the GRK2 inhibitor Gallein had no effect on the reduced SOM-induced response following repetitive SOM applications.